2021
DOI: 10.3389/fped.2021.726712
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Fitness Level of College Students Before and After Web-Based Physical Education During the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has been an emergency worldwide. Web-based physical education is a choice for college students to keep on their study. The aim of this study was to compare the data of physical fitness of college students before and after web-based physical education.Methods: All the students of 2018 and 2019 in Wuhan University of Technology who had taken the web-based physical education class in 2020 were included in this study. The records of annual physical fitness tests of all the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
6
24
2
1
Order By: Relevance
“…Moreover, this finding was inconsistent with a recent study revealing that college men’s pull-up performances increased during the lockdown [ 17 ]. This study indicated that pull-up performances increased by 25% among college students in Wuhan, China after social isolation [ 17 ].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Moreover, this finding was inconsistent with a recent study revealing that college men’s pull-up performances increased during the lockdown [ 17 ]. This study indicated that pull-up performances increased by 25% among college students in Wuhan, China after social isolation [ 17 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, this finding was inconsistent with a recent study revealing that college men’s pull-up performances increased during the lockdown [ 17 ]. This study indicated that pull-up performances increased by 25% among college students in Wuhan, China after social isolation [ 17 ]. Since the universities in this study and our study were both in China, participants’ duration of lockdown in the two studies was almost the same.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The authors also note that most schoolchildren did not follow the recommendations of teachers on the recommended minimum physical activity. Wei Xia et al [25] observed a decrease in the results of 50, 800 and 1000 m in boys and girls in China. The authors note the improvement of strength training in the exercises "Eurofit Sit Up Test", "Pull-Up Bars" for boys and "Squats Test" for girls.…”
Section: Discussionmentioning
confidence: 95%